Analisis Pendapatan Dan Faktor-Faktor Yang Mempengaruhi Usahatani Ubi Kayu Di Desa Pakuan Ratu - Zartika, Chicha; Apriyani, Marlinda; Saty, Fadila Marga; Trisnanto, Teguh Budi (LPPM Universitas Dharma Andalas, 2024)
Pakuan Ratu Village is the largest cassava producer in Pakuan Ratu District in Way Kanan Regency. This study aims to analyze the factors of cassava production and analyze the income of cassava farming in Pakuan Ratu village. Population taking technique using random sampling method. Determination of the number of samples using the Slovin formula with a significant level of 10%. The analytical method used is multiple linear regression analysis and farm income analysis. The results of this study based on the t-statistical test showed that land area (X1), seeds (X2), fertilizers (X3), and pesticides (X4) had a significant effect, while Labor (X5) had no significant effect on cassava production in the village. Pakuan Ratu, Pakuan Ratu District, Way Kanan. Based on the R Square value, it shows that cassava production in Pakuan Ratu Village is 94.9% influenced by variables of land area, seeds, fertilizers (urea, KCL, and NPK), pesticides, and labor. Analysis of the average income of cassava farming in Pakuan Ratu Village with an average production of 19,735 kg with a selling price of Rp. 1,200/kg obtained an average income of cassava farming in Pakuan Ratu Village of Rp. 8,829,623/farmer or Rp. 14,533 .791/ha which means that the income obtained by farmers can cover the total cost of Rp. 14,852,377/farmer or Rp. 21,064,857/ha used during production. Based on the calculation of the R/C Ratio and B/C Ratio, namely 1.59 and 0.59, it shows that cassava farming in Pakuan Ratu Village is profitable.